Apigenin induces ROS‐dependent apoptosis and ER stress in human endometriosis cells. Issue 4 (14th July 2017) - Park, Sunwoo; Lim, Whasun; Bazer, Fuller W.; Song, Gwonhwa
Abstract : Apigenin is a plant‐derived flavonoid having antiproliferative, anti‐inflammatory, and anti‐angiogenic properties in chronic and metabolic diseases, and cancers. However, the functional role of apigenin remains to be identified in human endometriosis that is a benign inflammatory disease causing infertility, dysmenorrhea, dyspareunia, and chronic abdominal or pelvic pain. In the present study, we determined the effects of apigenin on two well‐established human endometriosis cell lines (VK2/E6E7 and End1/E6E7). Apigenin reduced proliferation and induced cell cycle arrest and apoptosis in the both endometriosis cell lines. In addition, it disrupted mitochondrial membrane potential (MMP) which was accompanied by an increase in concentration of calcium ions in the cytosol and in pro‐apoptotic proteins including Bax and cytochrome c in the VK2/E6E7 and End1/E6E7 cells. Moreover, apigenin treated cells accumulated excessive reactive oxygen species (ROS), and experienced lipid peroxidation and endoplasmic reticulum (ER) stress with activation of the unfolded protein response (UPR) regulatory proteins. Furthermore, the apigenin‐induced apoptosis in endometriosis cells was regulated via the ERK1/2, JNK, and AKT cell signaling pathways. Taken together, apigenin is a potential novel therapeutic agent to overcome current limitations in the treatment to endometriosis. Abstract : Apigenin is a potential therapeutic substance, which disrupts MMP and induces excessive generation of ROS and ER stress through regulation of the ERK1/2 MAPK, JNK MAPK, and AKT signal transduction pathways, to inhibit proliferation and induce apoptosis in human endometriosis cells.